Having people over : a modern guide to planning, throwing, and attending every type of party - Fagan, Chelsea (Ten Speed Press, 2025)
In a world that often feels disconnected and transactional, there's nothing more radically hospitable than welcoming people into your space, your table, and your life. In this accessible, inviting book on hosting and entertaining, author Chelsea Fagan guides readers on creating moments worth staying in for. From designing the right space, to crafting a menu that won't keep you in the kitchen all night, to revitalizing the lost art of cultivating grown-up communities, this book will make you the perfect host at every budget. --